What has been talking on competence in health promotion in nursing education? - Silva, Kênia Lara (2015)
The development of skills in the training of health professionals has been discussed in the scientific literature in order to ensure quality services and has recently been the subject of important publications in the international arena. However, in Brazil it has few experiences and productions about the theme. The study aimed to analyze how competencies for health promotion in nursing education are configured. This is an integrative literature review in which were included eight articles, theses and dissertations published since 2000 in English, Spanish and Portuguese. The descriptors used for the search were: “health promotion”, “education based on skills” and “professional competence”. The analysis unearthed the following thematic categories: definition of competencies, skills and health promotion and teaching of skills in health promotion. The findings show that most of the literature is of international origin. Most guard resemblance to the powers of CompHP and Galway Consensus and present the definition of competence as a combination of three areas: attitude, knowledge and skills. Health promotion is addressed in disciplines such as public health, population health and health policy. It is evident that students experience the health promotion practice in the community. Moreover, the approach to promoting health in the final years of the course is indicated as more profitable than at the beginning because of the maturity (clinical and policy) of the students.